The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1192/pb.bp.107.018218
|View full text |Cite
|
Sign up to set email alerts
|

Crisis resolution and home treatment teams for older people with mental illness

Abstract: Aims and MethodWe examined the impact of a crisis resolution and home treatment teams (CRHTT) on hospital admission rates, bed days and treatment satisfaction among older people with mental illness and their carers. We compared these factors in the 6 months before the service started and 6 months after its introduction.ResultsThe CRHTT significantly reduced admissions (P<0.001), but there was no significant difference in the length of hospital stay as compared before and after the introduction of this servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 7 publications
2
27
0
Order By: Relevance
“…Crisis resolution home treatment provided by older people's mental health services now show reductions in unplanned admissions, discharge to care homes, length of stay and high user satisfaction. 1,24,25 General hospital liaison is a rare example of service development for older people, with services increasing from 27% of providers in 2003 26 to 84% of commissioning areas now, with 91% considered to provide equality of access and 82% of the 91% provided by older people's mental health services. Validity of this increase can be found in the National Audit of Dementia when 88% of general hospitals in England reported access to a liaison psychiatry service that can assess older people and 81% of those provided by a dedicated team.…”
Section: Discussionmentioning
confidence: 99%
“…Crisis resolution home treatment provided by older people's mental health services now show reductions in unplanned admissions, discharge to care homes, length of stay and high user satisfaction. 1,24,25 General hospital liaison is a rare example of service development for older people, with services increasing from 27% of providers in 2003 26 to 84% of commissioning areas now, with 91% considered to provide equality of access and 82% of the 91% provided by older people's mental health services. Validity of this increase can be found in the National Audit of Dementia when 88% of general hospitals in England reported access to a liaison psychiatry service that can assess older people and 81% of those provided by a dedicated team.…”
Section: Discussionmentioning
confidence: 99%
“…Ten references were included: three cohort studies, 170,189,190 one descriptive study, 27 one survey-related research study, 191 two theoretical papers 192,193 and three government policy documents. 23,194,195 Cohort studies and descriptive study…”
Section: Results: Literature Reviewmentioning
confidence: 99%
“…Dibben et al 190 found a statistically significant reduction in admissions 6 months after the introduction of the CRHTT. Sixty-nine per cent of referrals (n = 70) were admitted in the intervention group, compared with 100% (n = 65) in the comparison group (see Table 45).…”
Section: Number Of Admissionsmentioning
confidence: 99%
“…However, this raises issues of equity as there is no evidence that these groups would not benefit. Some CRTs extend their client age range beyond 65, and specialist home treatment services for elderly people have begun to develop, with some evidence that they can prevent admissions (Dibben 2008). Preliminary evidence suggests that CRTs can also prevent admission among people with personality disorders, and many services do work with this group (Cotton 2007).…”
Section: The Remit Of Crtsmentioning
confidence: 99%